Pemanfaatan Herpetofauna Sebagai Obat di Kota Jakarta dan Bandung - Hanny Herzegovina; Mirza D. Kusrini; Burhanuddin Masy’ud (The Ethnobiological Society of Indonesia, 2021)
Only few studies have investigated the use of wild animals, especially amphibian and reptile in big cities in Indonesia. We conducted market survey in Jakarta and Bandung to see the use of herpetofauna (amphibian and reptile) at traditional medicine sales centers by interviewing traders and consumers to get in-depth information on the species used and volume. There are 16 species of herpetofauna used as traditional medicines which consist of two species of amphibians and 14 species of reptiles. Most frequent used reptiles are snakes (cobra and reticulated python), monitor lizard and soft-shelled turtles, with main use is to treat skin diseases and increase stamina. Application of herpetofauna as a medicine could be in the form of oral consumption (i.e. satay, dry meat, frog leg meat, soup, capsules, flour) or topical medication (oil, ointment).